Raising awareness of the spread of Covid-19 among school children courseware / Muhammad Haikal Mazalan - Mazalan, Muhammad Haikal (2022)
The development of the Raising Awareness of The Spread of Covid-19 Among School Children Courseware is based on the Pamphlets of NORMA Baharu Di Sekolah and Circular Letter of Garis Panduan Pengurusan Pembukaan Sekolah provided by Ministry Of Education and Ministry Of Health. There are three objectives in developing this courseware which are to implement the standard operating procedures and guidelines on Covid-19 preventive measures among school children in interactive way, to design and develop a web-based health educational courseware guided by Schneiderman’s Golden Rules and to evaluate the usability of the courseware as education or training materials. Based on the pamphlet and Circular letters provided, two main topics are selected namely Apa Itu Covid-19?, and Panduan Keselamatan Di Sekolah. Simbol-simbol Covid-19 and Latihan are added as additional materials. There are three problem statements that trigger the proposal of courseware. The problem is the lack of interactive materials to enhance of the standard operating procedure in practice, school children rarely read informational pamphlets or brochures distributed among them and lastly, lack of proper health guidance from parents to children. The courseware applies the theory of Schneiderman’s Eight Golden Rules in its development process. A functionality testing has been conducted using the test cases and the result from the test cases about the overall function of the courseware is 100% passes. The test case form includes the activity, expected results, actual results, and pass or fail column. The developer who also acts as the tester would fill in the test case form in the pass or fails. The delivery content is presented by using multimedia elements which are animation, text, audio, video, and graphic. Hopefully, this courseware can serve as learning material for the school children to enhance the standard of Covid-19 proceedings in school area as a tools to prevent the spreading of Covid-19 among education clusters.